Structural characterization of the trees of a forest ejido of northwest Mexico - Graciano Avila, Gabriel; Alanís Rodríguez, Eduardo; Aguirre Calderón, Óscar Alberto; González Tagle, Marco Aurelio; Treviño Garza, Eduardo Javier; Mora Oliva, Arturo (Instituto de Ecología, A.C., 2017)
The objective of this study was to characterize the composition and structure of a forest ejido in the state of Durango. To this end, 10 sampling sites of 2500 m2 were established, within which a census was conducted of all tree species. On each individuals measurements of normal diameter (d1,30), total height (h), of crown diameter (dcopa) were made and the species to which each individual belonged was recorded. For each species the index of value importance family (IVIF), index of value importance (IVI), index value forestry were obtained and the total volume calculated. The Shannon (H´) and Margalef indices (DMG) were also calculated. In total 13 species, five genders and five families were recorded. This forest area had a density of 787 ind ha-1, a dominance (basal area) 22,93 m2 ha-1 and a crown cover of 8838 m2 ha-1. Pinus durangensis had the highest value of importance index with 35,69% of IVIrel and the largest value forestry index with 48,96% IVFrel. With all of the above, quantitative elements of the timberline in a heterogeneous forest of the Sierra Madre Occidental were provided.